2020
DOI: 10.1016/j.mayocp.2020.05.009
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Evidence Synthesis Programs to Respond to a Pandemic

Abstract: The coronavirus disease 2019 (COVID-19) pandemic requires making rapid decisions based on sparse and rapidly changing evidence. Evidence synthesis programs conduct systematic reviews for guideline developers, health systems clinicians, and decision-makers that usually take an average 6 to 8 months to complete. We present a framework for evidence synthesis programs to respond to pandemics that has proven feasible and practical during the COVID-19 response in a large multistate health system employing more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…The literature updates were sent by email to the TRP team and consisted of two components: a link to the Treatment section of NLM LitCovid website 11 ( https://www.ncbi.nlm.nih.gov/research/coronavirus/docsum?filters=topics.Treatment ) updated, evidence synthesis documents from the Robert D. and Patricia E. Kern Center for the Science of Health Care Delivery's COVID-19 Rapid and Systematic Reviews Repository. 12 …”
Section: Methodsmentioning
confidence: 99%
“…The literature updates were sent by email to the TRP team and consisted of two components: a link to the Treatment section of NLM LitCovid website 11 ( https://www.ncbi.nlm.nih.gov/research/coronavirus/docsum?filters=topics.Treatment ) updated, evidence synthesis documents from the Robert D. and Patricia E. Kern Center for the Science of Health Care Delivery's COVID-19 Rapid and Systematic Reviews Repository. 12 …”
Section: Methodsmentioning
confidence: 99%
“…The program developed a dedicated framework in response to the COVID-19 pandemic that included methods to conduct and index rapid reviews and repositories of studies published on the pandemic since the first reported case. 1 To date, the Kern Center's evidence synthesis program has indexed more than 2000 publications on this topic.…”
Section: The Strategiesmentioning
confidence: 99%
“…Individual studies have limited ability to summarize the current state of research; thus, many efforts have been made to conduct systematic reviews and synthesize the presently available results for policymaking during the pandemic. The evidence synthesis is achieved via meta‐analyses, which play a critical role in developing new research by determining whether the proposed study is necessary and helping design the study 12,13 . Systematic reviews and meta‐analyses are considered of the highest quality and can be viewed as a lens through which evidence is evaluated 14‐17 …”
Section: Introductionmentioning
confidence: 99%
“…The evidence synthesis is achieved via meta-analyses, which play a critical role in developing new research by determining whether the proposed study is necessary and helping design the study. 12,13 Systematic reviews and meta-analyses are considered of the highest quality and can be viewed as a lens through which evidence is evaluated. [14][15][16][17] However, systematic reviews and meta-analyses do not always provide a rationale for their methodology; if not used properly, they could produce ambiguous results and exacerbate research errors.…”
Section: Introductionmentioning
confidence: 99%